Rethinking Original Order and Personal Records - Meehan, Jennifer (Archivaria, 2010)
This article presents a different theoretical approach to considering and implementing the concept of original order in the arrangement and description of personal records. As currently conceived, original order does not address the physical realities of personal records and results in approaches that, whether in extending the concept by analogy or rejecting it outright, fail to adequately contextualize personal records. Concentrating on the theoretical aspects of the concept and the spirit behind the principle, this article rethinks original order as a conceptual framework for elucidating context, and suggests how it facilitates a top-down approach for analyzing a body of personal records regardless of whether or not there is a consistent, discernible order. By focusing attention on the relationships between records and activities, original order as a conceptual framework enables the archivist to better interpret and represent key factors relating to personal recordkeeping, custodial history, and archival intervention, which over time shape the meanings of a personal fonds. RÉSUMÉ Cet article présente une approche théorique différente pour considérer et appliquer le concept de l’ordre original dans le classement et la description de documents personnels. Tel qu’il est présentement entendu, l’ordre original ne tient pas compte de la réalité physique des documents, ce qui mène vers une approche qui, soit en extrapolant le concept par analogie ou en le rejetant carrément, ne permet pas de contextualiser adéquatement les documents personnels. En se concentrant sur les aspects théoriques du concept et l’esprit de base de ce principe, l’auteure redéfinit l’ordre original en tant que cadre conceptuel pour élucider le contexte et explique comment ce cadre facilite une approche du général au spécifique pour analyser un ensemble de documents personnels, peu importe s’il y a un ordre apparent ou logique. En centrant l’attention sur les liens entre les documents et les activités, l’ordre original comme cadre conceptuel permet à l’archiviste de mieux interpréter et représenter les facteurs clés relatifs à la gestion de documents personnels, à l’histoire de la garde des documents et à l’intervention archivistique, ces facteurs qui, avec le temps, influencent l’interprétation d’un fonds personnel.